2021
DOI: 10.1186/s12906-020-03182-1
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin protects radiation-induced liver damage in rats through the NF-κB signaling pathway

Abstract: Background Curcumin has been demonstrated to exert anti-oxidant, anti-fibrotic, anti-inflammatory, and anti-cancer activities. This study was conducted to observe the effect and inner mechanism of curcumin in rats with radiation-induced liver damage (RILD). Methods Thirty SD rats were classified into Control, Radiation group and Curcumin (Cur) + Radiation group (n = 10 in each group). The changes in body weight of the rats were observed on the 3rd,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 52 publications
(17 reference statements)
3
24
0
Order By: Relevance
“…Hematoxylin and Eosin (H&E) staining was performed to examine the pathology of rat liver. Referred to previous study ( Li W. et al, 2021 ), briefly, fresh rat liver tissues were fixed with 4% paraformaldehyde, dehydrated and embedded in paraffin after routine dehydration. Subsequently, sliced into 4-μm sections with Automatic Slicer (Shanghai Leica Instrument Co. Ltd., Shanghai, China), followed by dewaxing and H&E staining.…”
Section: Methodsmentioning
confidence: 99%
“…Hematoxylin and Eosin (H&E) staining was performed to examine the pathology of rat liver. Referred to previous study ( Li W. et al, 2021 ), briefly, fresh rat liver tissues were fixed with 4% paraformaldehyde, dehydrated and embedded in paraffin after routine dehydration. Subsequently, sliced into 4-μm sections with Automatic Slicer (Shanghai Leica Instrument Co. Ltd., Shanghai, China), followed by dewaxing and H&E staining.…”
Section: Methodsmentioning
confidence: 99%
“…It has also been demonstrated that curcumin reduces tumor invasion and metastatic growth by, for example, reducing the activity of matrix metalloproteinases (MMPs) 2 and 9, or blocking nuclear translocation of nuclear factor kappa B (NFκB) by inhibiting the inhibitor of kappaB kinase [ 11 , 12 , 13 ]. This molecular pathway is also involved in the prevention of liver damage after exposure to radiotherapy [ 16 ] by regulating oxidative stress damage and reducing the accumulation of reactive oxygen species, which are well known to contribute to tumor progression by promoting cell transformation, proliferation, and the survival of tumor cells [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that CUR attenuates Pb-induced hepatorenal toxicity via chelating activity and inhibition of oxidative stress. Li et al (2021) studied the effect of CUR on liver damage induced by radiation in rats.…”
Section: Discussionmentioning
confidence: 99%